Fetal inheritance of GP*Mur causing severe HDFN in an unrecognized case of maternal alloimmunization. Issue 4 (14th February 2020) - Mallari, Rose A.; Chan, Ada; Powers, Richard J.; Pandipati, Santosh; Bensing, Kathleen M.; Biese, Danielle; Denomme, Gregory A.
Abstract : BACKGROUND: The clinical and laboratory features of hemolytic disease of the newborn can be challenging to diagnose during pregnancy in the apparent absence of a blood group antibody. Low‐frequency antibodies go undetected due to the lack of appropriate antigen‐positive reagent red blood cells (RBCs). CASE REPORT: A pregnant woman of Southeast Asian descent was referred to a maternal‐fetal medicine outpatient clinic due to a complicated obstetric history and a negative antibody screen. This initial visit at 29 weeks and 0 days' gestational age (GA) was unremarkable. A hydropic infant, born at 29 weeks and 5 days' GA, succumbed on the seventh day of life. Comprehensive laboratory testing was performed after birth. The hospital blood bank performed a maternal antibody identification. Direct antiglobulin test was performed on the cord blood. A reference laboratory confirmed an anti‐Mi a, performed paternal Mi a phenotyping, and identified a hybrid glycophorin B‐A‐B GP*Mur allele. DISCUSSION: Maternal alloimmunization to low‐frequency antigens remains a challenge. Southeast Asians make up a significant percentage in some US locations. Worldwide reports on the frequency of maternal alloimmunization of the MNS system can be used to guide the use of specific reagent RBCs for testing. Such strategies rely on the identification of blood donor units for reagent manufacture and use in perinatal antibody screens. CONCLUSION: The incidence of Mi a and related antibodies is significant among Southeast Asians. In North America, prenatal antibody screening cells are not routinely chosen to match this population. The clinical and societal implications are discussed. Abstract : See editorial on page 659–662,  in this issue